Masschusetts - Zaroulis, Nancy L. (Fawcett Columbine, 1991)
A panoramic saga based on the history of the New England state begins as an orphan boy, Bartholomew Revell, steps off the "Mayflower," and follows his descendants through four hundred years of uprisings, witch-hunts, wars, and other challenges
62642
Keywords: American Literature; Historical Fiction